MXene coated PZS-C gel structure membrane electrode and preparation method and application thereof
Through the preparation of MXene@PZS-C gel structural membrane electrode, the problems of complex preparation and limited adsorption capacity of existing uranyl adsorption materials have been solved, and the effect of efficient electrochemical removal of uranyl ions has been achieved, and the application prospects have been achieved.
Patent Information
- Application Number
- CN202510414691.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-04
AI Technical Summary
The existing uranyl adsorbent materials have problems such as complex preparation process, limited adsorption capacity and insufficient stability. Especially when electrochemical separation of uranyl ions, the utilization rate of conductivity and active sites is not high.
The MXene@PZS-C gel structure membrane electrode was adopted, and the MXene nanosheets were compounded with microspherical PZS through electrostatic self-assembly and vacuum-assisted filtration preparation method to form a multi-stage porous structure. The PZSC skeleton was used to expand the layer spacing to prevent stacking and improve the exposure and stability of active sites.
The ability to efficiently remove uranyl ions is achieved, with a maximum removal amount of 3375.44 mg/g, which is significantly higher than other electrochemical materials. It has a simple preparation process, low cost and excellent circulation performance.
Smart Images

Figure CN120247026A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a membrane electrode, in particular to a MXene@PZS-C gel structure membrane electrode and a preparation method thereof, and also relates to an application in the electrochemical removal of uranium, belonging to the technical field of electrochemical uranium removal. Background Technique
[0002] Long-term problems such as improper uranium ore mining, insufficient nuclear energy development, and improper radioactive waste treatment have led to the widespread presence of uranium in the environment. The chemical toxicity and potential bioaccumulation of U(VI) pose a great health risk, and long-term exposure may cause serious immune diseases and malignant tumors. Therefore, it is crucial to effectively remove uranium from wastewater and the natural environment.
[0003] In recent years, square wave exchange (SWE) technology, as a new electrochemical method for removing or separating uranium from sewage and seawater, has attracted the research interest of many researchers. Using a high-frequency square wave voltage, heavy metal / radionuclide ions can migrate quickly to the vicinity of the working electrode, with good kinetic characteristics. Compared with capacitive deionization (CDI) technology, adsorption, extraction, catalysis, and ion exchange methods, the square wave exchange method shows good economy and environmental adaptability. The working electrode used in the square wave exchange method belongs to the category of traditional electrodes, and its main components are three, namely a conductive substrate, an active substance, and an additive. Among them, the active substance is mainly a conductive non-Faraday material and a redox-active Faraday material. During the electrochemical removal process, the redox-active Faraday material can capture specific heavy metal / radionuclide ions through redox reactions, with significant selective ion separation. As a typical material of non-Faraday materials, carbon and its derivative materials have better conductivity, cycle stability, and active material utilization rate. Generally, excellent carbon materials are required to have a large specific surface area (SSA), excellent conductivity, and a developed pore structure.
[0004] However, the SWE technology still has key application problems. While the conductive carrier gives the electrode material a stable active space, it limits the selection of active materials. The first is the use of additives (binders: PVDF, PTFE, naphthol, etc.; conductive agents: graphene, graphdiyne, etc.). Although it ensures the stability of the electrode system, it will cause an irreversible decrease in conductivity and hinder the transfer of electrons. The second is that the additive components severely restrict the release of the active space of the active substance, causing pore adhesion and blockage. The third is that the addition of extra conductive agents makes the system stability poor. These problems have greatly troubled researchers for a long time.
[0005] MXene is a new type of two-dimensional material, and its structural formula is M n X n-1T, where M is a transition metal such as Ti, Mo, Nb, and V, X is carbon and nitrogen, and T is a capping group such as -OH, -O, and halogen. It is obtained by etching away the main group element A from the layered ceramic material MAX (chemical formula M n AX n-1 ). It is usually prepared by a two-step method of hydrofluoric acid / tetramethylammonium hydroxide or a one-step method using hydrochloric acid / lithium fluoride. Among them, Ti3C2T x , as a member of the MXene family, has become a star in two-dimensional materials due to its simple preparation process, low cost, and wide application fields. Its excellent specific surface area and abundant surface functional groups give it significant advantages in adsorbing heavy metal elements and radionuclides. Although the membranes composed of Ti3C2T x nanosheets are still in the primary stage of adsorption research, their excellent electrical conductivity, flexibility, and structural strength make them a strong candidate to replace current collectors. However, the spontaneous stacking phenomenon of Ti3C2T x membranes limits their application in the field of electrochemical separation of radionuclides.
[0006] In the existing technology, U(VI) is adsorbed by bonding active substances to current collectors. For example, Chinese Patent Application (Publication No.: CN116212829A) discloses a preparation method of an electric field-assisted Ti3C2T x / MOFs uranyl adsorption material. Using Ti3C2T x , amidoximated diaminomaleonitrile, metal ions, and 2-methylimidazole as raw materials, an electric field-assisted amidoximated Ti3C2T x / MOFs composite electrode with antibacterial and high-efficiency uranium adsorption performance was prepared for electroadsorbing U(VI) in water. A maximum physicochemical adsorption capacity of about 800 mg / g and an electrochemical removal capacity of U(VI) of 2000 mg / g were obtained within 60 min. The adsorption capacity of this adsorbent is higher than that of previous electroadsorbing U(VI), but the process of preparing the electrode is complex, and it is difficult to further improve the adsorption capacity due to the limitation of adsorption sites. Summary of the Invention
[0007] Aiming at the defects of the existing uranyl adsorption materials, the first object of the present invention is to provide a MXene@PZS-C gel structure composite membrane electrode, which uses a conductive polyphosphazene-derived carbon (PZSC) skeleton to fix MXene nanosheets, shows good stability, can effectively expand the interlayer spacing of MXene to prevent its stacking, and has a fixed pore structure to further open active sites. When used for the electrochemical separation of uranyl ions, its maximum removal amount is as high as 3375.44 mg / g, which is generally higher than other electrochemical uranium removal materials and has good application prospects.
[0008] The second object of the present invention is to provide a preparation method of an MXene@PZS-C gel structure composite membrane electrode, which has the advantages of simple operation, low cost, strong stability, etc.
[0009] The third object of the present invention is to provide an application of an MXene@PZS-C gel structure composite membrane electrode. The MXene@PZS-C gel structure composite membrane electrode is used for removing uranyl ions in wastewater by a square wave exchange method, showing good removal ability and excellent cycling performance.
[0010] In order to achieve the above technical objects, the present invention provides a preparation method of an MXene@PZS-C gel structure membrane electrode, which comprises the following steps:
[0011] 1) Etch MAX powder with an HCl-LiF mixed solution to exfoliate and form an MXene nanosheet suspension; or, after etching MAX powder with an HF solution, add tetramethylammonium hydroxide for intercalation to form an MXene nanosheet suspension;
[0012] 2) Dissolve hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone, add triethylamine, and carry out a condensation reaction under ultrasonic action to obtain microspherical PZS;
[0013] 3) Stir and mix the MXene nanosheet suspension with microspherical PZS, and deposit it on a substrate by vacuum-assisted filtration to form a film body. The film body is obtained by vacuum freeze-drying and calcination to obtain an MXene@PZS-C gel structure membrane electrode.
[0014] The preparation method of the MXene@PZS-C gel structure membrane electrode provided by the present invention, the specific process schematic diagram refers to Figure 1 , first etch and delaminate MAX powder to obtain an MXene nanosheet doped material, then self-assemble the MXene nanosheets and microspherical PZS through electrostatic interaction to form a disordered stacked three-dimensional structure, and then further carbonize to obtain MXene@PZS-C (MPC). The excellent electrochemical performance and film-forming ability of the MXene nanosheets themselves lay a foundation for the preparation of self-supporting membrane materials, and the introduction of a conductive polyphosphazene-derived carbon (PZSC) skeleton can effectively expand the interlayer spacing of the MXene nanosheets, prevent their ordered stacking, fix the pore structure, further open their active sites, and greatly improve the ability of the MXene nanosheets to adsorb uranyl ions.
[0015] The key to the technical solution of the present invention lies in the introduction of polyphosphazene polymer. On the one hand, microspherical PZS is used to achieve the self-assembly of MXene nanosheets. Through the electrostatic interaction between the two, the disordered stacking of MXene nanosheets is realized. Moreover, the microspherical PZS is filled between the MXene nanosheet layers, which can expand the spacing between MXene nanosheets, prevent the ordered stacking of MXene nanosheets, and at the same time construct a special three-dimensional pore structure, which can expose more adsorption active sites of MXene nanosheets. On the other hand, the microspherical PZS forms a microporous structure after high-temperature carbonization, thus constructing a hierarchical porous structure. At the same time, the microspherical PZS is transformed into a hard carbon skeleton to prevent the overall volume collapse, improve the stability of the adsorption material, and the organic matter volatilized during the heating process of the microspherical PZS overflows, which is beneficial to the formation of pores in MXene nanosheets and avoids their spontaneous ordered stacking. Thirdly, the polyphosphazene polymer has a high covalent cross-linked structure and rich co-doping of N, P, and S elements. Its derived carbon PZSC is an excellent conductive carbon skeleton and a good carrier for heteroatom doping, which is beneficial to improving the electrochemical adsorption performance of MXene nanosheets for uranyl ions.
[0016] The MAX powder of the present invention can be selected from Ti3AlC2, Ti4AlC3, V2AlC, Nb2AlC, Mo2Ga2C, etc., and the MXene nanosheets formed by exfoliating the MAX powder are T4C3T x nanosheets, Ti3C2T x nanosheets, V2CT x nanosheets, Nb2CT x nanosheets and Mo2CT x nanosheets, etc.
[0017] As a preferred solution, the concentration of LiF in the HCl-LiF mixed solution is 60-100 mg / mL, and the concentration of HCl is not less than 8 mol / L. More preferably, it is concentrated hydrochloric acid with a concentration of 8-10 mol / L.
[0018] As a preferred solution, the mass concentration of the HF solution is 20-49%.
[0019] As a preferred solution, the ratio of the MAX powder to the HCl-LiF mixed solution is measured according to the mass ratio of MAX to LiF of 1:1.5-2.
[0020] As a preferred solution, the ratio of the MAX powder to the HCl-LiF mixed solution is measured according to the mass ratio of MAX to LiF of 1:1.5-2.
[0021] As a preferred solution, the mass ratio of the MAX powder to the HF solution is 1:20-25.
[0022] As a preferred embodiment, the mass ratio of the tetramethylammonium hydroxide to the MAX powder is 1:10 to 40.
[0023] As a preferred embodiment, the molar ratio of the hexachlorocyclotriphosphazene to the 4,4'-dihydroxydiphenyl sulfone is 1:3.0 to 3.2. The molar ratio of hexachlorocyclotriphosphazene to 4,4'-dihydroxydiphenyl sulfone mainly affects the molecular weight of the polyphosphazene. It is difficult to obtain high-molecular-weight polyphosphazene if either ratio is too high or too low.
[0024] As a preferred embodiment, the conditions for the condensation reaction are as follows: the ultrasonic power is 150 to 210 W, the frequency is 35 to 45 Hz, the temperature is 30 to 50 °C, and the time is 2 to 5 hours. During the condensation reaction process of the present invention, with the aid of ultrasonic action, it is not only beneficial to promote the polymerization reaction process, but also beneficial to obtain a uniform microspherical PZS material. The microspherical PZS can effectively expand the interlayer structure of MXene, prevent stacking, and release a larger specific surface area and active sites.
[0025] As a preferred embodiment, the mass ratio of the MXene nanosheet suspension to the microspherical PZS material is 4 to 6:2 to 4. If the proportion of MXene nanosheets is too high, it will cause the ordered stacking of some MXene nanosheets and affect the film-forming performance. If the proportion of MXene nanosheets is too low, the adsorption performance of the membrane electrode will deteriorate.
[0026] As a preferred embodiment, the conditions for the calcination are as follows: under a protective atmosphere, heat to 400 to 500 °C at a heating rate of 3 to 8 °C / min and calcine for 1 to 3 h. Through high-temperature calcination, the microspherical PZS is carbonized into a hard carbon skeleton, greatly improving the stability of the membrane material. At the same time, the carbon skeleton formed by the microspherical PZS has a porous structure and is doped with abundant heteroatoms such as nitrogen, sulfur, and phosphorus, which is beneficial to improving its conductivity and adsorption activity.
[0027] The particle size of the MAX powder of the present invention is 100 to 400 mesh.
[0028] The stirring reaction conditions of the present invention are to carry out a constant-temperature stirring reaction at a temperature of 35 to 100 °C for 30 to 120 h.
[0029] The present invention also provides a MXene@PZS-C type gel structure membrane electrode, which is obtained by the preparation method.
[0030] The present invention also provides an application of a MXene@PZS-C type gel structure membrane electrode, which is used as a working electrode in a two-electrode system for electrochemically adsorbing uranyl ions in an electrochemical adsorption solution system.
[0031] As a preferred solution, the dual - electrode system adopts the square - wave exchange electrochemistry method. By using the square - wave exchange electrochemistry method, the electrochemical adsorption and separation performance of uranyl ions can be greatly improved, and the energy consumption and the occurrence of side reactions such as water electrolysis can be reduced.
[0032] In the present invention, the MXene@PZS - C - type gel structure membrane electrode is added to the solution to be treated containing uranyl ions, and a square - wave exchange dual - electrode system supported by an arbitrary waveform generator is used to react at room temperature for a corresponding time under a certain voltage.
[0033] As a preferred solution, the pH of the solution system is adjusted to 2.0 - 7.0.
[0034] As a preferred solution, the concentration range of uranyl ions in the solution system is 5 - 1000 mg / L.
[0035] As a preferred solution, the working alternating voltage of the square - wave exchange electrochemistry method is 0 and - 5V, the working frequency is 100 - 500 Hz (the preferred working frequency is 300 - 500 Hz), the duty cycle is 0 - 100% (the preferred duty cycle is 40 - 60%), and the initial phase is 0 - 360° (the preferred initial phase is 180°).
[0036] Compared with the prior art, the beneficial technical effects brought by the technical solution of the present invention are as follows:
[0037] (1) The preparation process of the MXene@PZS - C composite membrane electrode of the present invention is by electrostatic self - assembly and vacuum - assisted filtration to form a membrane, which has the advantages of simple preparation method, low cost, strong stability, etc.
[0038] (2) For the MXene@PZS - C composite membrane electrode of the present invention, by introducing PZSC, the pore collapse of MXene is effectively inhibited, the layer spacing of MXene is increased and fixed, a conductive network is formed, ion migration is promoted, the spontaneous stacking of MXene is restricted, and more adsorption active sites are exposed.
[0039] (3) For the MXene@PZS - C - type gel membrane electrode of the present invention, MXene is used as the electrode skeleton, and carbonized PZS is used as the structural support and active site to support the interlayer space of MXene, establish a conductive network, improve the ion accessibility, and enhance the electrochemical removal ability.
[0040] (4) The MXene@PZS - C composite membrane electrode of the present invention has obtained a large removal capacity, low energy consumption, and a stable system under the technical support of the square - wave exchange method.
[0041] (5) The MXene@PZS-C composite membrane electrode of the present invention shows good electrochemical uranium ion removal ability, stable structure and excellent cycling performance in the uranium removal experiment of wastewater supported by the square wave exchange method.
[0042] (6) The MPC, a MXene@PZS-C gel-like membrane electrode of the present invention, is easy to recover insoluble uranium solids of sodium uranate with the support of the square wave exchange method, convenient for recycling and enrichment, simplifies the removal and elution steps, and reduces the cycling cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Synthesis schematic diagram of MPC-1 prepared in Example 1.
[0044] Figure 2 SEM image of MPC-1 prepared in Example 1.
[0045] Figure 3 XRD pattern of MPC-1 prepared in Example 1.
[0046] Figure 4 Performance graph of MPC-1 prepared in Example 1 for adsorbing uranyl ions at different pH values.
[0047] Figure 5 Performance graph of MPC-1 prepared in Example 1 for adsorbing uranyl ions at different concentrations.
[0048] Figure 6 Performance graph of MPC-1 prepared in Example 1 for removing uranyl ions by physical and chemical adsorption and SWE method.
[0049] Figure 7 Performance graph of MPC1-MPC5 prepared in Example 1 for electrochemical uranium removal.
[0050] Figure 8 Performance graph of MPC-1 prepared in Example 1 for electrochemical removal of uranyl ions at different working voltages.
[0051] Figure 9 Removal amount graph of MPC-1 prepared in Example 1 for electrochemical uranium removal.
[0052] Figure 10 SEM and EDS images of MPC-1 prepared in Example 1 after the electrochemical uranium removal experiment.
[0053] Figure 11 Performance graph of MPC-1 prepared in Example 1 for electrochemical removal of uranyl ions from simulated wastewater.
[0054] Figure 12 Performance graph of MPC-1 prepared in Example 1 for cycle stability. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0056] Example 1
[0057] 1) Preparation of MXene nanosheet suspension:
[0058] ①: 2g Ti3AlC2 was washed with deionized water and ethanol respectively, transferred to a vacuum oven at 60°C, dried for 24h and stored. 40mL of HCl (9mol / L) was added to a polytetrafluoroethylene beaker, 3.2g LiF was weighed and slowly added to the above solution, and after sufficient stirring, it was transferred to a 40°C water bath and stirred at 600rpm for 30min; within half an hour, the dried Ti3AlC2 was slowly added to the above solution and stirred for 60h. The obtained black liquid was washed with a centrifuge to remove unreacted LiF and other substances, and the residue was washed with dilute hydrochloric acid (2mol / L), centrifuged several times with deionized water (5000rpm) until the upper layer could not be centrifuged, and transferred to an ultrasonic ice bath under argon conditions for 4 hours, and then centrifuged at 3500rpm for 20 minutes. The resulting suspension was stored at 4°C under argon to avoid oxidation. It is recorded as MXene-1 suspension.
[0059] ②: 2g Ti4AlC3 was washed with deionized water and ethanol respectively, transferred to a vacuum oven at 60°C, dried for 24h and stored. 40mL of HF (40%) was added to a polytetrafluoroethylene beaker, and Ti4AlC3 powder was slowly added to the above solution. After sufficient stirring, it was transferred to a 60°C water bath and stirred at 600rpm for 60h. The obtained black liquid was washed with a centrifuge to remove unreacted HF and other substances, and then 50mL of tetramethylammonium hydroxide (20%) was added, stirred at room temperature for 24 hours, and the residue was washed with dilute hydrochloric acid (2mol / L), and then centrifuged several times with deionized water (5000rpm) until the upper layer could not be centrifuged and pH = 7, and transferred to an ultrasonic ice bath under argon conditions for 4 hours, and then centrifuged at 3500rpm for 20 minutes. The resulting suspension was stored at 4°C under argon to avoid oxidation. It is recorded as MXene-2 suspension.
[0060] ③: 1 g of V2AlC was washed with deionized water and ethanol respectively, transferred to a vacuum furnace at 60 °C, dried for 24 h and stored. 20 mL of HF (40%) was added to a polytetrafluoroethylene beaker, and the V2AlC powder was slowly added to the above solution. After stirring well, it was transferred to a water bath at 80 °C and stirred at 600 rpm for 72 h. The resulting black liquid was washed with a centrifuge to remove unreacted HF and other substances. Subsequently, 50 mL of tetramethylammonium hydroxide (20%) was added and stirred at room temperature for 24 h. The residue was washed with dilute hydrochloric acid (2 mol / L), and then centrifuged several times with deionized water (5000 rpm) until the upper layer could not be centrifuged and the pH = 7. It was transferred to an ultrasonic ice bath under argon for 4 h, and then centrifuged at 3500 rpm for 20 min. The resulting suspension was stored at 4 °C under argon to avoid oxidation. It was denoted as MXene-3 suspension.
[0061] ④: 1 g of Mo2Ga2C was washed with deionized water and ethanol respectively, transferred to a vacuum furnace at 60 °C, dried for 24 h and stored. 20 mL of HF (20%) was added to a polytetrafluoroethylene beaker, and the Mo2Ga2C powder was slowly added to the above solution. After stirring well, it was transferred to a water bath at 60 °C and stirred at 600 rpm for 120 h. The resulting black liquid was washed with a centrifuge to remove unreacted HF and other substances. Subsequently, 50 mL of tetramethylammonium hydroxide (20%) was added and stirred at room temperature for 24 h. The residue was washed with dilute hydrochloric acid (2 mol / L), and then centrifuged several times with deionized water (5000 rpm) until the upper layer could not be centrifuged and the pH = 7. It was transferred to an ultrasonic ice bath under argon for 6 h, and then centrifuged at 3500 rpm for 20 min. The resulting suspension was stored at 4 °C under argon to avoid oxidation. It was denoted as MXene-4 suspension.
[0062] ⑤: 2 g of Nb2AlC was washed with deionized water and ethanol respectively, transferred to a vacuum furnace at 60 °C, dried for 24 h and stored. 40 mL of HF (20%) was added to a polytetrafluoroethylene beaker, and the Nb2AlC powder was slowly added to the above solution. After stirring well, it was transferred to a water bath at 50 °C and stirred at 600 rpm for 30 h. The resulting black liquid was washed with a centrifuge to remove unreacted HF and other substances. Subsequently, 50 mL of tetramethylammonium hydroxide (20%) was added and stirred at room temperature for 24 h. The residue was washed with dilute hydrochloric acid (2 mol / L), and then centrifuged several times with deionized water (5000 rpm) until the upper layer could not be centrifuged and the pH = 7. It was transferred to an ultrasonic ice bath under argon for 3 h, and then centrifuged at 3500 rpm for 20 min. The resulting suspension was stored at 4 °C under argon to avoid oxidation. It was denoted as MXene-5 suspension.
[0063] 2) Preparation of spherical PZS powder:
[0064] 0.1217 g of hexachlorocyclotriphosphazene and 0.2628 g of 4,4'-dihydroxydiphenyl sulfone were added to 100 mL of acetonitrile. The mixture was stirred for 10 min. Subsequently, 3 mL of triethylamine was added, and the mixture was treated in an ultrasonic water bath at a constant temperature of 40 °C, 190 W, and 40 Hz for 3 h. Subsequently, the solution was transferred to a 10 mL centrifuge tube and centrifuged at 8000 rpm for 2 - 3 times, 3 - 5 min each time, to separate the precipitate. The precipitate was washed successively with ethanol and deionized water to remove impurities. Finally, the washed precipitate was vacuum dried at 60 °C for 12 h to finally obtain white powder-like PZS.
[0065] 3) Preparation of MXene@PZS-C type gel structure membrane electrode:
[0066] The Mxene-1 suspension, Mxene-2 suspension, Mxene-3 suspension, Mxene-4 suspension, and Mxene-5 suspension were respectively mixed with PZS in a mass ratio of 5:3 and continuously stirred for 4 h to ensure thorough mixing of the two. The resulting grayish-black suspension was then deposited on the base membrane by vacuum-assisted filtration. After 24 h of vacuum freeze-drying at -50 °C, products MP-1 to MP-5 were obtained. MP-1 to MP-5 were placed in a tubular furnace and heated to 450 °C at a heating rate of 5 °C / min under the protection of nitrogen and calcined at this temperature for 2 h. The finally obtained products were named MPC-1 to MPC-5.
[0067] Example 2
[0068] 1) Preparation of MXene nanosheet suspension: Refer to the preparation process of the MXene-1 suspension in Example 1.
[0069] 2) Preparation of spherical PZS powder: Refer to the preparation process of Example 1.
[0070] 3) Preparation of MXene@PZS-C type gel structure membrane electrode:
[0071] The MXene nanosheet suspension was mixed with PZS in mass ratios of 5:1, 5:2, 5:3, and 5:4 and continuously stirred for 4 h to ensure thorough mixing of the two. The resulting grayish-black suspension was then deposited on the base membrane by vacuum-assisted filtration. After 24 h of vacuum freeze-drying at -50 °C, product MP was obtained. MP was placed in a tubular furnace and heated to 450 °C at a heating rate of 5 °C / min under the protection of nitrogen and calcined at this temperature for 2 h. The finally obtained products were respectively named MPC1-A, MPC1-B, MPC1-C, and MPC1-D.
[0072] Example 3
[0073] 1) Preparation of MXene nanosheet suspension: Refer to the preparation process of MXene-1 suspension in Example 1.
[0074] 2) Preparation of spherical PZS powder: Refer to the preparation process of Example 1.
[0075] 3) Preparation of MXene@PZS-C gel-like structure membrane electrode:
[0076] Mix the MXene nanosheet suspension and PZS in a mass ratio of 5:3 and stir continuously for 4 h to ensure thorough mixing. The resulting grayish-black suspension is then deposited on the base membrane by vacuum-assisted filtration. After 24 h of vacuum freeze-drying at -50 °C, the product MP is obtained. MP is placed in a tubular furnace and heated to 400 °C, 450 °C, and 500 °C at a heating rate of 5 °C / min under the protection of nitrogen, and calcined at this temperature for 2 h. The final products are named MPC1-400, MPC1-450, and MPC1-500 respectively.
[0077] Figure 1 is the schematic diagram of the synthesis route of MPC-1.
[0078] Figure 2 is the SEM image of MPC-1. There is an obvious gel-like network structure between MXene layers. The carbonized PZS can effectively link the lamellae to form a bridge for ion transport and improve the overall structural stability.
[0079] Figure 3 is the XRD pattern. Ti3C2T x The (002) crystal plane representing the graphite phase appears at 6.2°. Ti3C2T x After compounding and carbonizing with PZS, the graphite phase (002) crystal plane and (100) crystal plane of carbonized PZS are found at 20° and 37°, proving the successful preparation of the composite material MPC-1.
[0080] Conventional adsorption experiment:
[0081] Under the conditions of pH = 6, uranyl ion C0 = 100 mg / L, t = 300 min, and MXene:PZS = 5:3, the adsorption capacities of MPC-1 to MPC-5 are 501.57, 343.54, 297.33, 431.54, and 222.21 mg / g respectively. The adsorption performance of MPC-1 is the most prominent.
[0082] Under the conditions of pH = 6, uranyl ion C0 = 100 mg / L, and t = 300 min, the uranium adsorption capacities of MPC1-A to MPC1-D prepared with different MXene:PZS ratios of 5:1, 5:2, 5:3, and 5:4 are 204.23 mg / g, 191.22 mg / g, 501.57 mg / g, and 242.35 mg / g respectively. The mass ratio of 5:3 can significantly balance the interlayer space and structural stability. Too little PZS results in still strong intermolecular hydrogen bonding and tight adhesion, while too much PZS leads to poor structural stability and broken electron transport paths.
[0083] Under the conditions of pH = 6, uranyl ion C0 = 100 mg / L, t = 300 min, and MXene:PZS = 5:3, the uranium adsorption capacities of MPC1-400 to MPC1-500 carbonized at 400 °C, 450 °C, and 500 °C are 365.22 mg / g, 399.02 mg / g, and 389.23 mg / g respectively. When the carbonization temperature is 400 °C, the decomposition of PZS is incomplete, resulting in residual organic matter and blocked interlayer pores, hindering the mass transfer process. When the carbonization temperature is 500 °C, excessive sintering leads to large-scale agglomeration of PZS and the collapse of the pore structure, restricting the interlayer spacing and the release of active sites. Therefore, 450 °C is the optimal temperature.
[0084] Example 4
[0085] Physicochemical adsorption of uranyl ions by the MXene@PZS-C composite membrane electrode MPC-1.
[0086] Figure 4 Effect of different pH values on the uranium removal performance of MPC-1 (pH = 6, v / m = 5, uranyl ion C0 = 100 mg / L, t = 300 min): In the preferred pH range of 2 - 7, the MPC-1 composite membrane exhibits higher uranium adsorption performance than the precursor MP, monomer PZS, and Ti3C2T x . This phenomenon is attributed to the hierarchical porous structure of MPC-1, which has a large specific surface area and outstanding ability to expose active sites. The uranium adsorption capacity of the four materials, especially MPC-1, is the most prominent at pH = 6. The reasons are as follows: ① When pH < 6, the degree of protonation in the solution is high, and a large number of hydrogen ions occupy the adsorption sites, resulting in low adsorption performance; ② When pH > 6, the typical uranyl cation species begin to transform into uranyl anion species, which repel the negative charge shown on the material surface, leading to a decrease in adsorption performance. Therefore, MPC-1 has the highest removal capacity at all pH values.
[0087] Figure 5Effect of different concentrations on the uranium(VI) removal performance of MPC-1 (pH = 6, v / m = 5, initial uranium(VI) concentration C0 = 100 mg / L, t = 300 min): In the selected uranium(VI) solutions with concentrations ranging from 10 to 200 ppm, the electrolyzed MPC1 composite membrane (501.57 mg / g) showed higher uranium adsorption performance than the precursor MP, monomer PZS, and Ti3C2T x (119.24 mg / g, 204.29 mg / g, and 318.45 mg / g). Due to the hierarchical porous structure, MPC-1 has open interlayer spaces with good mass transfer ability, which can accommodate high-concentration uranium(VI) solutions for transmission in the void structure, increasing the collision probability between active sites and uranium(VI) ions. Therefore, it exhibits the largest adsorption capacity.
[0088] Example 5
[0089] Comparison of physicochemical adsorption and electrochemical removal of uranium(VI) by MXene@PZS-C composite membrane electrode MPC-1.
[0090] Figure 6 Effect of adsorption and SWE methods on the uranium(VI) removal performance of MPC-1 (pH = 6, initial uranium(VI) concentration C0 = 100 mg / L): The solid-liquid ratios of the adsorption method and the SWE method are 1:5 and 1:20, respectively. After processing by absorbance normalization, the uranium(VI) removal amounts are compared. Before 180 min, there is no significant difference between the two methods, which is attributed to the unsaturation of adsorption sites. After 180 min, the adsorption capacity of the adsorption method tends to saturate, but the SWE method is still increasing rapidly. Since the SWE method converts positively charged uranium(VI) ions into electrically neutral insoluble substances (Na2O(UO3·H2O) x ), the occupied adsorption sites are re-exposed due to the change in the electrical properties of the adsorbed substances, and finally, it shows 3375.44 mg / g, significantly higher than the adsorption method (399.02 mg / g / ), indicating an important improvement in the uranium removal ability of the SWE method for MPC-1.
[0091] Example 6
[0092] Electrochemical removal of uranium(VI) by MXene@PZS-C composite membrane electrode MPC.
[0093] As Figure 7 shown, Ti3C2T x , T4C3T x , V2CT x , Mo2CT x , Nb2CT xThe uranium removal performances of the MXene@PZS-C composite membranes MPC-1, MPC-2, MPC-3, MPC-4, and MPC-5 prepared from nanosheets and PZS were compared under the conditions of (t = 750 min, pH = 6, v / m = 20, C0 = 200 mg / L, Frequency = 400 Hz). Their removal amounts were 1978.21 mg / g, 2056.33 mg / g, 1543.62 mg / g, 1105.75 mg / g, and 3375.44 mg / g respectively. The Ti3C2T x The MXene@PZS-C composite membrane prepared from nanosheets and PZS exhibited the most prominent performance.
[0094] Figure 8 The following is the effect of different voltages on the electrochemical uranium removal performance of MPC-1 (t = 750 min, pH = 6, v / m = 20, C0 = 200 mg / L, Frequency = 400 Hz): When the voltage was -5 V, MP showed a maximum adsorption amount of 989.12 mg / g, while the maximum adsorption amount of MPC-1 reached 3375.44 mg / g. Since MP contains PZS components and has poor conductivity, the uranium removal process under voltage driving was hindered. However, the conductivity of MPC-1 after carbonization was significantly improved. Under the action of the electric field, MPC-1 with good conductivity not only has a larger specific surface area but also exposes more active sites, so it is beneficial to the migration and enrichment of U(VI). Therefore, under the same conditions, MPC1 can obtain a higher removal amount.
[0095] Under the conditions of V = -5 V, pH = 6, v / m = 20, C0 = 200 mg / L, and Frequency = 400 Hz, MP
[0096] and the curve of the electrochemical uranium removal performance of MPC-1 changing with time are as follows Figure 9 shown. MPC-1 demonstrated excellent removal ability at higher concentrations. In a U(VI) solution with a concentration of 1000 mg / L, the electrochemical removal amount of MPC-1 was as high as 8901.46 mg / g, far exceeding that of MP, which was 1779.53 mg / g. Its high conductivity and optimized pore structure enable MPC-1 to have higher efficiency and capacity during the separation process.
[0097] Figure 10 The SEM and EDS maps of the electrode surface after the electrochemical uranium removal test of MPC-1 are shown. Uranium adhered to the material surface in the form of sodium uranate hydrate (Na2O(UO3·H2O) x )), which is convenient for recycling and enrichment.
[0098] Example 7
[0099] Study on the Cycling Stability and Selectivity of MXene@PZS-C Composite Membrane Electrode MPC-1
[0100] As Figure 11 , the competitive ions were Zn, Pb, Gd, Cs, Cu, Ni, Al and Co respectively, with a concentration of 50 mg / L, which was 5 times the concentration of U(VI). When the competitive ions were present, the electrochemical removal amounts of U(VI) by MP were 34.00 mg / g, 23.43 mg / g, 61.33 mg / g, 21.22 mg / g, 25.40 mg / g, 36.44 mg / g, 49.12 mg / g and 41.61 mg / g, and those by MPC-1 were 195.92 mg / g, 196.32 mg / g, 199.91 mg / g, 199.32 mg / g, 197.83 mg / g, 194.60 mg / g, 200.00 mg / g and 200 mg / g. MPC-1 had a higher electrochemical removal efficiency for U(VI).
[0101] As Figure 12 shown, MPC-1 was subjected to cyclic elution to test its stability, and 0.01 mol / L dilute nitric acid was selected as the eluent. After repeating the cyclic operation five times, the removal efficiencies of MP and MPC-1 were 66.32% and 94.83% respectively. MPC-1 had good reusability.
[0102] The embodiments described above only represent several preferred embodiments of the present invention. The description is relatively specific and detailed, but it does not limit the present invention. It should be noted that for those skilled in the art, the present invention can also have various changes and modifications. Any modifications, equivalent replacements, improvements, etc. made within the concept and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A preparation method of an MXene@PZS-C gel structure membrane electrode, characterized in that: It includes the following steps: 1) Etch the MAX powder with an HCl-LiF mixed solution, and strip it to form a MXene nanosheet suspension; Alternatively, etch the MAX powder with an HF solution, and then add tetramethylammonium hydroxide for intercalation to form a MXene nanosheet suspension; 2) Dissolve hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone, add triethylamine, and carry out a condensation reaction under ultrasonic action to obtain microspherical PZS; 3) Stir and mix the MXene nanosheet suspension with the microspherical PZS, and deposit it on a substrate by vacuum-assisted filtration to form a film body. The film body is vacuum freeze-dried and calcined to obtain a MXene@PZS-C gel structure film electrode.
2. The preparation method of a MXene@PZS-C gel structure film electrode according to claim 1, wherein: The concentration of LiF in the HCl-LiF mixed solution is 60-100 mg / mL, and the concentration of HCl is not less than 8 mol / L; the mass concentration of the HF solution is 20-49%.
3. The preparation method of a MXene@PZS-C gel structure film electrode according to claim 1 or 2, wherein: The ratio of the MAX powder to the HCl-LiF mixed solution is measured according to the mass ratio of MAX to LiF of 1:1.5-2; The mass ratio of the MAX powder to the HF solution is 1:20-25; The mass ratio of the tetramethylammonium hydroxide to the MAX powder is 1:10-40.
4. The preparation method of an MXene@PZS-C class gel structure membrane electrode according to claim 1, characterized in that: The molar ratio of the hexachlorocyclotriphosphazene to the 4,4'-dihydroxydiphenyl sulfone is 1:3.0-3.
2.
5. The preparation method of an MXene@PZS-C class gel structure membrane electrode according to claim 1, wherein: The conditions of the condensation reaction are: ultrasonic power is 150-210 W, frequency is 35-45 Hz, temperature is 30-50 °C, and time is 2-5 hours.
6. The preparation method of an MXene@PZS-C class gel structure film electrode according to claim 1, characterized in that: The mass ratio of the MXene nanosheet suspension to the microspherical PZS is 4-6:2-4.
7. The preparation method of an MXene@PZS-C gel structure membrane electrode according to claim 1, characterized in that: The conditions of the calcination are: under a protective atmosphere, heat it to 400-500 °C at a heating rate of 3-8 °C / min, and calcine for 1-3 h.
8. A MXene@PZS-C gel structure membrane electrode, characterized in that: Obtained by the preparation method according to any one of claims 1-7.
9. Application of an MXene@PZS-C class gel structure membrane electrode according to claim 8, characterized in that: As a working electrode of a two-electrode system for electrochemically adsorbing uranyl ions in an electrochemical adsorption solution system.
10. The MXene@PZS-C gel structure membrane electrode according to claim 9, characterized in that: The two-electrode system adopts square wave exchange electrochemistry method.
Citation Information
Patent Citations
Preparation method of electric field assisted Ti3C2Tx / MOFs uranyl adsorption material with bacteriostasis and selectivity
CN116212829A
Cited By
Cobalt single atom loaded polyphosphazene / MXene self-supporting electrode and preparation method and application thereof
CN122079313A